MEMBANGUN PEMAHAMAN PAJAK BAGI PELAKU USAHA MIKRO, KECIL DAN MENENGAH DI SEMARANG - Hermawan Triono; Juli Ratnawati; Anna Sumaryati; Enny Susilowati Mardjono (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
Understanding tax regulations is a fundamental obligation for all taxpayers, including SMEs. Taxpayers have a tendency to be disobedient when they do not understand tax regulations. SMEs must understand the concept of tax, calculate tax correctly, pay tax on time, and report tax return. Therefore, assistance and training regarding the fulfilment obligations for SMEs are necessary to improve their understanding and compliance. This community service aims to assist and provide training on tax calculation to SMEs in Jomblang, Semarang. The method is by doing presentations, training in calculating tax and consulting conducted by lecturers who have competence in the field of taxation. The results of the training show that SMEs finally understand the tax concept and are willing to carry out their tax obligations.